MERAB MAMARDASHVILI VS THE SOVIET MENTALITY - Lali Zakaradze (European Scientific Journal, ESJ, 2014)
In the present paper the author analyzes the thought of Georgian philosopher Merab Mamardashvili (1930-1990) in the context of philosophy of culture. According to Mamardashvili, philosophy and thinking is identical to life. He tried to break through the closed borders of the Soviet system and bring the experience of other cultures into the Soviet philosophy. Mamardashvili’s thought represents an attempt of original synthesis of different (French, German and Russian) cultural traditions. He criticized harshly everyday life of a Soviet citizen. With his criticism he significantly promoted the development of critical consciousness in the Soviet Union.